TRANSFORMING RURAL EDUCATION WITH DIGITAL ASSESSMENT TOOLS: A CASE STUDY OF SOCRATIVE IN SAROLANGUN, INDONESIA - Saleh Yaakub; Wawan Joko Pranoto; Ika Safitri Windiarti; Rida Priyanti (Jurnal Abdimas UM Jambi, 2025)
Purpose: This study explores the implementation of Socrative, a digital assessment tool, to enhance teaching and learning in rural primary schools in Sarolangun, Indonesia. It addresses persistent challenges such as limited digital literacy, inadequate infrastructure, and low student engagement. The study aligns with the Indonesian government’s "Merdeka Belajar" curriculum, emphasizing the integration of modern technologies into education. Methods: A mixed-methods approach was employed, incorporating qualitative and quantitative data collection. Teachers participated in training workshops covering Socrative’s functionalities, followed by a three-month classroom implementation phase. Data were gathered through pre- and post-intervention surveys, classroom observations, and interviews with teachers and administrators. Descriptive statistics and thematic analysis were used to evaluate the intervention’s impact. Results: The findings indicate a significant improvement in teacher digital literacy, with proficiency levels increasing from 35% to 85% post-intervention. Student engagement in classrooms using Socrative rose by 40% compared to traditional methods. However, challenges such as limited internet connectivity and device availability were identified as barriers to scalability. Despite these challenges, the study demonstrated the feasibility of integrating digital tools in resource-constrained environments. Conclusions: The implementation of Socrative proved effective in addressing digital literacy and engagement gaps in rural education.